Effect of Density of Air Line and Height of Used Cookimg Oil on Burning Quality of Oil Palm Soil Waste Biobriquettes - Zulvi Arwana Fakih; Saipul Bahri Daulay; Sumono Sumono; Ainun Rohana (Universitas Sumatera Utara, 2013)
Palm oil mill solid waste resulting from CPO production process is channeled into pond waste (Cooling Pond I). It is usually thrown to the ground so that it can contaminate the environment. This study was aim to utilize the oil palm waste as briquettes. Briquettes is one of the alternative to replace oil. Research was done by completely randomized factorial design with 2 factors i.e : density of air line (0,4, 0,8, and 1,2 cm) and Height of used cooking oil (2, 2,5, and 3 cm). Parameters observed were heating time, oil volume, and sootness. The results showed that the density of air line had a highly significant effect on the heating time, volume of oil and had no effect on the sootnes. Height of used cooking oil had a significant effect on sootness and had no effect on the heating time and volume of oil. The best treatment combination was L1T2 (0,4 centimeters density of air line and 2,5 centimeters Height of used cooking oil) with equipment heatimg time of 43,90 minute and 1,79 gr sootness. Key words: Briquettes, density of air line, Height of used cooking oil centration, Oil palm solid waste.